The effects of OLL1073R-1 yogurt intake on influenza incidence and immunological markers among women healthcare workers: a randomized controlled trial. Issue 12 (18th November 2019) - Kinoshita, Tetsu; Maruyama, Koutatsu; Suyama, Keiko; Nishijima, Mariko; Akamatsu, Kimiko; Jogamoto, Akiko; Katakami, Kikumi; Saito, Isao
Abstract : This randomized controlled trial did not show the effects of OLL1073R-1 yogurt intake on influenza prevention and NK cell activity enhancement. However, a significant increase in IFN-γ production was demonstrated. Abstract : Probiotics have been expected to enhance human immune function. The aim of this study was to evaluate the effects of dietary intake of yogurt fermented with Lactobacillus delbrueckii ssp. bulgaricus OLL1073R-1 (OLL1073R-1) on the prevention of influenza during winter and on the activation of immunological markers among women healthcare workers. 961 women aged 20–71 years were randomly assigned to either the yogurt group ( n = 479) or the control group ( n = 482). Participants in the yogurt group consumed a 112 mL yogurt drink fermented with OLL1073R-1 every day for 16 weeks, whereas those in the control group consumed no yogurt during this period. All participants were instructed not to consume any other kinds of yogurt or fermented dairy products throughout this trial. The cumulative incidence rate of influenza was measured, and immunological markers were examined at the baseline and after 16 weeks. No significant difference in the incidence rate of influenza was found between the two groups (cumulative incidence rates of flu: yogurt 7.5% and control 7.7%). Natural killer (NK) cell activity did not show a significant intervention effect ( p = 0.11), whereas the intervention effect on serum interferon gamma (IFN-γ) production was significant ( p = 0.03). Other immunological markers did not show significant intervention effects. Consumption of OLL1073R-1 yogurt did not show a significant preventive effect against influenza or a significant enhancement in NK cell activity. However, intake of this yogurt showed an increase in IFN-γ production.